Using stated preference methods to inform public health decision making: Evidence from Croatia - Nikolina Dukić Samaržija (Management : Journal of Contemporary Management Issues, 2021)
Croatia has recognised the importance of prevention programmes in the field of public health, although their effectiveness is not satisfactory due to the low population response, which has a negative impact on the rationalisation of public spending. One of the possible solutions is to consider the stated preferences of the target population. Therefore, the main objective of this study is to evaluate the use of stated preference methods in improving public health prevention programmes. For the purpose of the study, a questionnaire was designed using three different methods - Discrete Choice Experiment (DCE), Contingent Rating method (CR) and Best-Worst Scaling method (BWS). This study shows that the attributes of the Croatian cervical cancer screening programme are significantly associated with the respondents' utility level, which in turn is related to women's response. Since BWS, DCE, and CR measure the same construct - utility - we can say that convergent validity partially confirms the external validity of the methods. The author concludes that it is necessary to implement market principles, i.e. the demand-side analysis using stated preference methods, in the planning, implementation and re-evaluation of public health programmes.